Hambatan Penataan Aparatur Sipil Negara Berbasis Kompetensi (Studi pada DLH Provinsi Jawa Timur) - Rosyida, Luthfiyah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
The structuring of State Civil Apparatus (ASN) in Indonesia is directed at the placement of ASN based on competence. However, there were still many problems with the placement of ASN that did not match their competence. This study uses qualitative method with descriptive type and aims to explain the inhibiting factors in the implementation of competency-based ASN structuring and the efforts that can be made to overcome them. The data in the study were obtained from the results of observations, interviews and documentation studies which were then processed using an interactive data analysis model. The results showed that the inhibited to competency based ASN structuring in DLH East Java Province consisted of: (a) internal factors, including: leadership, organizational needs and human resources; and (b) external factors, including: the weak role of external institutions and the limitations in the implementation of education and training. To overcome these inhibiting factors, commitment from various parties is needed, such as: organizational leaders, HR, BKD of East Java Province and BPSDM of East Java Province, and it is necessary to formulate new policies regarding ASN structuring that are more adaptive, comprehensive and implementable.